Role and mechanism of lncRNA under magnetic nanoparticles in atrial autonomic nerve remodeling during radiofrequency ablation of recurrent atrial fibrillation. Issue 2 (1st February 2022) - Jiang, Weifeng; Xu, Ming; Qin, Mu; Zhang, Daoliang; Wu, Shaohui; Liu, Xu; Zhang, Yu
ABSTRACT: It aimed to investigate the mechanism of magnetic nanoparticles (MNPs) on atrial fibrillation and effect of n-isopropyl acrylamide coated MNPs (NIPA-co-MN) on the treatment of atrial fibrillation. Ten beagles weighing 20 − 25 kg were randomly divided into test group and control group. Dogs with atrial fibrillation were set as test group, and non-atrial fibrillation dogs as control group. The expression of long non-coding RNA (lncRNA) differentially expressed in the right anterior adipose pad in atrial fibrillation and non-atrial fibrillation dogs was detected by high-throughput sequencing. The relationship between lncRNA and cardiac autonomic nerve remodeling (CANR) was explored. In addition, 20 beagles weighing 20–25 kg were selected to study the therapeutic effect of n-isopropylacrylamide magnetic nanoparticles (NIPA-co-MN) on atrial fibrillation, and statistical analysis was performed. The volume and number of new neurons in the anterior right fat pad of atrium of test group were larger than the control group. The test group dogs produced 45 brand-new lncRNA, including 15 up-regulated transcripts and 30 down-regulated transcripts. MNPs injection can slow down the reduction of ventricular rate in right inferior ganglion plexus. The anterior right ganglion plexus resulted in a reduced amplitude of sinus tachyarrhythmia. This study provided references for the discovery of new diagnostic biomarkers or therapeutic targets and for the treatment of patients with atrial fibrillation.